Microeconomic Features Socialist Transition and Capitalist Economie - Ravshan, , Urunov (International Journal of Psychosocial Rehabilitation, 2020)
This paper discusses the main features of a socialist and capitalist economies, monetary policy in a socialist economy, matters related to accounting and business analysis, issues of improving the system of criteria for determining signs of economic insolvency of enterprises, microeconomic problems of countries with economies in transition.